PERAN PEMBINA REMAJA MASJID DALAM MENANAMKAN NILAI-NILAI KARAKTER KEAGAMAAN PADA REMAJA DI MASJID NURUL HIDAYAH DESA GARECCING KABUPATEN SINJAI - Nurfidayani,; Syamsidar,; Hamid, Ilham (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2023)
The journal created aims to describe how the role of mosque youth choaches in instilling religious character values in adolescents. This study used a descriptive qualitative research type located at the Nurul Hidayah Mosque Gareccing Village Sinjai Regency. This study used the Islamic guidance and counseling approach. The primary data source for this research is mosqou youthsupervisorrs as a key informant. additional informants namely mosqou youth and congregation. The secondary data sources of this research are books, internet, and documentation. This research data collection methods are observation, interviews and documentation. Analysis of this research data through data reduction, data presentation and drawing conclusions. The results of this study indicate that the efforts of mosqou youth coaches in instilling religious character values in adolescents at the Nurul Hidayah Mosque Gareccing Village Sinjai District, namely 1. Take a persuasive approach 2. Identifty problems 3. Carry out masqou activities. The inhibiting factors of the coach in instilling religious character values in adolescents are 1 lack of self awareness from adolescents 2. Lack of time efficiency 3. Lack of adolescent interest in religious activities 4. Lack of attention from parents.